PERAN GURU DALAM MENGENALKAN GERAKAN SHALAT MELALUI MEDIA FLASH CARD BERGAMBAR PADA ANAK USIA 5-6 TAHUN DI TK AL-MUHAJIRIN CILEGON, BANTEN - Ayu Ningsih Husaini; Siti Khosiah; Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research titled "The Role of Teachers in Introducing Prayer Movements Thru Illustrated Flash Cards to 5-6 Year Old Children at Al-Muhajirin Kindergarten, Cilegon, Banten." The role of teachers in teaching and learning activities is very important in creating engaging activities that are suitable for the characteristics of early childhood. Early childhood children require concrete learning media, such as illustrated flash cards, which can be used to help introduce prayer movements to children. The purpose of this research is to describe the role of teachers in introducing prayer movements thru illustrated flash cards to children aged 5-6 years at TK Al-Muhajirin Cilegon and to assess the prayer movement abilities of children aged 5-6 years. This research uses a qualitative method with a descriptive approach. The research subjects consist of imtak center teachers and children aged 5–6 years at TK Al-Muhajirin Cilegon, Banten. Data collection techniques were carried out thru observation, interviews, and documentation. Data analysis was conducted thru the stages of data reduction, data presentation, and conclusion drawing. The validity of the data is obtained thru triangulation of sources and techniques. The research results show that teachers play the roles of planners, implementers, facilitators, motivators, and evaluators in the activities of introducing prayer movements. The teacher utilizes illustrated flash cards to help children recognize the sequence of prayer movements more easily and engagingly. The use of such media can enhance children's attention, interest, and enthusiasm during the learning process. In addition, children find it easier to understand and practice the movements of prayer correctly according to the teacher's instructions. The success of the learning process is supported by the use of engaging media, teaching methods that align with the child's development, direct demonstrations by the teacher, and consistent teacher guidance. Based on the research results, it can be concluded that the role of the teacher in introducing prayer movements thru illustrated flash cards is very important and influential in the understanding and ability of 5–6-year-old children to perform prayer movements as part of the prayer program. Illustrated flash cards have proven to be an effective tool in assisting the religious learning process for young children.